Partial Visual Loss Affects Self-reports of Hearing Abilities Measured Using a Modified Version of the Speech, Spatial, and Qualities of Hearing Questionnaire - Kolarik, Andrew J.; Raman, Rajiv; Moore, Brian C. J.; Cirstea, Silvia; Gopalakrishnan, Sarika; Pardhan, Shahina (Frontiers in Psychology, 2017)
We assessed how visually impaired (VI) people perceived their own auditory abilities using an established hearing questionnaire, the Speech, Spatial and Qualities of Hearing Scale (SSQ), that was adapted to make it relevant and applicable to VI individuals by removing references to visual aspects while retaining the meaning of the original questions. The resulting questionnaire, the SSQvi, assessed perceived hearing ability in diverse situations including the ability to follow conversations with multiple speakers, assessing how far away a vehicle is, and the ability to perceptually segregate simultaneous sounds. The SSQvi was administered to 33 VI and 33 normally sighted participants. All participants had normal hearing or mild hearing loss, and all VI participants had some residual visual ability. VI participants gave significantly higher (better) scores than sighted participants for: (i) one speech question, indicating less difficulty in following a conversation that switches from one person to another, (ii) one spatial question, indicating less difficulty in localizing several talkers, (iii) three qualities questions, indicating less difficulty with segregating speech from music, hearing music more clearly, and better speech intelligibility in a car. These findings are consistent with the perceptual enhancement hypothesis, that certain auditory abilities are improved to help compensate for loss of vision, and show that full visual loss is not necessary for perceived changes in auditory ability to occur for a range of auditory situations. For all other questions, scores were not significantly different between the two groups. Questions related to effort, concentration and ignoring distracting sounds were rated as most difficult for VI participants, as were situations involving divided-attention contexts with multiple streams of speech, following conversations in noise and in echoic environments, and judging elevation or distance and externalizing sounds. The questionnaire has potential clinical applications in assessing the success of clinical interventions and setting more realistic goals for intervention for those with auditory and/or visual losses. The results contribute towards providing benchmark scores for VI individuals.